Peran Customer Relationship Management (CRM) Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Pt.Pegadaian Cabang Mojokerto - Pradanis, Muhammad Nandito; Andriani, Nurita (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
Many people consider that marketing and sales have the same meaning, but in reality, these two aspects are different parts that are not separate from a company. Marketing emphasizes how a company strives to find potential customers and retain them from switching to competitors. This study aims to examine the effect of Customer Relationship Management (CRM) on customer loyalty by considering the role of customer satisfaction as a mediating variable. The method used in this research is quantitative with a survey approach. Data was collected through questionnaires distributed to customers of PT. Pegadaian Mojokerto Branch and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results of the study show that CRM has a significant positive effect on customer satisfaction, and customer satisfaction has a significant positive effect on customer loyalty. Additionally, customer satisfaction mediates the effect of CRM on customer loyalty. The conclusion of this study is that effective CRM implementation can increase customer loyalty through improved customer satisfaction.